2D Hybrid Halide Perovskites: Structure, Properties, and Applications in Solar Cells. Issue 43 (30th September 2021) - Wu, Guangbao; Liang, Rui; Zhang, Zhipeng; Ge, Mingzheng; Xing, Guichuan; Sun, Guoxing
Abstract: 2D metal‐halide perovskites have attracted intense research interest due to superior long‐term stability under ambient environments. Compared to their 3D analog, the alternate arrangement of organic and inorganic layers leads to forming a multilayer quantum well (MQW), which endows 2D perovskites with anisotropic optoelectronic properties. In addition, the spacer layer functions as a hydrophobic barrier to effectively prevent 2D perovskite films from ion migration and moisture penetrating, thus realizing outstanding stability. Recently, 2D perovskites have been widely developed with abundant species. The stunning photovoltaic performance with the coexistence of long‐term stability and high‐power conversion efficiency (PCE) has been realized in 2D perovskite solar cells (PSCs), which paves an avenue for commercialization of PSCs. This review begins with an introduction of crystal structure and crystallization kinetics to illustrate the unique layer characters in 2D perovskites. Then, electron structure, excitons, dielectric confinement, and intrinsic stability properties are discussed in detail. Next, the photovoltaic performance based on recent Ruddlesden–Popper (RP), Dion–Jacobson (DJ), and alternating cations in the interlayer (ACI) phase 2D‐PSCs is comprehensively summarized. Finally, the confronting challenges and strategies toward structural design and optoelectronic studies of 2D perovskites are proposed to offer insight into the advanced underlying properties of this family of materials. Abstract : This review presents state‐of‐the‐art developments on 2D metal‐halide perovskite solar cells. The basic crystal structure, properties, and device photovoltaic performance on 2D perovskites are discussed in detail. Besides, the confronting challenges and corresponding strategies are proposed to offer insight into the underlying properties of this family of materials.